Influence Before and After Early Mobilization of Changes in Pain Levels in Sectio Cesarea Postoperative Clients at Royal Prima Hospital in 2020 - Ma Hongjun; Florenly Florenly; Liena Liena; Fioni Fioni (Budapest International Research and Critics University, 2021)
Sectio Caesarea is artificial labor in which the fetus is born through an incision in the front wall of the abdomen and the uterine wall. The number of Sectio Caesarea patients in Indonesia has exceeded the recommended threshold of the Department of Health > 20%. Surgery can cause postoperative pain in the client, this pain is usually felt 12 to 36 hours after surgery. One of the management of non-famakological treatment of post-section caesarean section pain treatment is early mobilization. Early mobilization aims to accelerate wound healing, improve circulation, and prevent venous static. The purpose of this study was to determine the influence before and after early mobilization of changes in pain levels in postoperative clients of sectio cesarea. This type of research is descriptively correlational, One Group Pretest-Postest, conducted at RSU Royal Prima Medan Petisah, North Sumatra from September to November 2020. The study population ± 43 people. The number of samples using the formula Slovin, so 36 samples were obtained. The selection of samples with non-probability sampling is consecutive sampling. Analysis of data, with a univariate, bivariate, meaningful limit of 0.05 with t-dependent test (paired t-test).The results, the change in pain level score of the pre-test test results of the mean value 3.22, at the time of the post-test test the mean value is 2.17. So the result of the value Z = -6,128 then p-value as much as 0.000 < 0.05 so that it was concluded Ho was rejected and Ha received. Concluded there is an influence of early mobilization of pain changes in postoperative clients sectio caesarea in the room of RSU Royal Prima in 2020.